Epidemiological evolution of COVID-19 in the State of Piauí in 2 months - Costa, Rafael Everton Assunção Ribeiro da (2020)
COVID-19 is a disease caused by the new viral strain of the Coronaviridae Family (Sars-Cov-2), which appeared in China's Hubei province in December 2019 and has been spreading rapidly around the world ever since. Thus, in view of the importance of Sars-Cov-2 infection for the current world scenario, which is also reflected in Piauí, and due to the relevance of epidemiological data for the establishment of more effective Public Health policies, this study aimed to analyze the evolution epidemiological analysis of COVID-19 cases in the state of Piauí in 2 months. This is an ecological, retrospective study, carried out using secondary data. The average mortality rate, bed occupancy and social isolation were calculated, with correlations between them using Pearson's coefficient and statistical significance assessment. In the analyzed period (2020), 5,101 cases and 164 deaths were reported, with a mortality rate of 34.4/1000 in April and 31.9/1000 in May. Inverse relationships were observed between the number of cases and the mortality rate (r = -0.491, p = 0.049), between average bed occupation and social isolation (r = -0.415, p = 0.001) and between isolation average social status and the number of reported cases (r = -0.329, p = 0.048). The results reinforce the importance of social isolation as a means of coping with COVID-19 in Piauí.